No room for squares: A political economy of Blue Note records - May, Christopher (Jazz Research Journal, 2007)
Blue Note records retains a reputation for excellent music packaged stylishly for a hip audience. This article suggests its longevity has been achieved through the conjunction of four elements. Firstly, Alfred Lion and Francis Wolff were respected for their (mainly black) artists, avoiding the exploitative culture of other jazz labels to ensure important artists did their best work for Blue Note. Secondly, they established a house style that has become emblematic for jazz overall. Thirdly, and coincidently, the period when Blue Note was most active documenting jazz music has become the period regarded by many as the pinnacle of jazz attainment. Lastly, these factors have been exploited by a series of owners who have sought to reinforce the brand of Blue Note. The interaction of these four elements ensures that Blue Note remains the jazz label that most people, jazz fans and others, are familiar with.